Stones, Bones, Groans and Moans - Rajani, Sana Zehra; Kaware, Bhupeshkumar; Gokhale, Shefali (International Journal of Human and Health Sciences (IJHHS), 2024)
Primary hyperparathyroidism (PHPT) is characterized by elevated serum calcium and parathyroid hormone (PTH) levels. This condition often remains undiagnosed, leading to severe renal and skeletal complications. We present three cases highlighting the importance of early detection and treatment. A 56-year-old woman presented with a femur fracture and recurrent renal calculi. Hypercalcemia, elevated PTH, and nephrocalcinosis confirmed PHPT. Parathyroidectomy and fracture treatment were performed. A 34-year-old hypertensive woman with flank pain had a right ureteric calculus and hypercalcemia. Imaging revealed a parathyroid adenoma. Ureteroscopy and DJ stenting resolved the calculus. A 62-year-old diabetic with urinary tract infection and renal calculi had hypercalcemia and elevated PTH. Parathyroid adenoma was detected, but surgery was declined. Clinical presentations of PHPT vary, including asymptomatic hypercalcemia, osteoporosis, and renal stones. Renal manifestations range from polydipsia to nephrolithiasis and renal dysfunction. Hypercalciuria contributes to stone formation, but not all patients develop stones. Technetium (99mTc) sestamibi aids in parathyroid scintigraphy, enhancing localization accuracy, along with ultrasonography. Screening, however, is not recommended without surgical plans. The disease's underdiagnosis is linked to insufficient biochemical screening. Increased awareness, suspicion, biochemical screening, and early intervention are essential for preventing these complications. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S34